Plan de negocios para la creación de una empresa dedicada al servicio de mensajería y Courier en la ciudad de Quevedo, año 2012. - Rizo Chonana, Lorena Natividad (2013)
The business activity is to provide a package delivery service in the city of Quevedo added value; this will need to create an enterprise under the administrative guidelines that establish a business plan for the fulfillment of the objectives. Vision: To be a competitive company in the medium term, in the Courier service and meeting the needs, requirements and demands of users with efficiency, effectiveness and efficiency. Mission: To provide a courier service and Courier that meets the demands of users with timely and appropriate responses and human talent trained in their area of expertise. It requires a total investment of USD 14.000,00 of those which USD 6.977.22 correspond to investment of active fixed, and USD 7.022.78 to work capital, as a result, in the analysis of the five year-old flows, considering a rate of discount of 15%, the one VAN that it generates this operation it is of $45.627.97, being a positive result what means that the project is viable. Another indicator that has allowed to check the feasibility of the project, is the TIR, which is of 94.26% above the opportunity cost, the analysis of Benefit Cost is of 4,26 that it overcomes in great magnitude the base that is 1 what represents an excellent investment opportunity.